Management of pregnancy in a University Hospital: a 6-year study - Schupp, Tânia Regina; Miyadahira, Seizo; Kahhale, Soubhi; Zugaib, Marcelo (Revista do Hospital das Clínicas, 2000)
In order to evaluate the obstetric care in the Obstetric Clinic of the Gynaecology and Obstetrics Department of University of São Paulo, the authors present a survey of the management of pregnancy during the 6-year period from 1993 to 1998. The number of deliveries increased during the study by 45% over the 6 years. During this same period the number of fetal deaths was 526 (4.48%), but there was a significant decrease (p < 0.05) in the incidence of fetal death. However, there was no concomitant increase in the proportion of pregnant women with prenatal care that could explain this improvement. Incidence of premature labor also decreased considerably. The authors believe that the increment in the number of deliveries was due mainly to the increasing number of pregnant women referred to our service. The efforts made by the service towards decreasing the time of hospitalization of both newborns in the nursery and the mothers in the hospital made this possible. Despite the increasing number of deliveries, there was a significant improvement in the management of pregnancy during the period of study. This improvement may be a consequence of the standardization of a protocol of management of pregnancy based on the recent progress in scientific and technological knowledge.